EFEKTIVITAS PENINGKATAN KEMAMPUAN PROFESIONAL GURU SMK DI KABUPATEN ACEH BESAR - Megawati Megawati (JURNAL SERAMBI ILMU, 2012)
Abstacs: Professional ability step-up teacher is done to increase science and teacher skill. This observational approaching is kualitatif's approaching. Data collecting tech is observation, interview, and studi documents. Subject is research it is headmaster, headmaster representative, majorschairman / studi's program, supervisor, senior teacher and MGMP. Result observationaling to point out that abilities increasing program professional teacher be arranged to side school and is performed activity thru supervision, training, seminar, diklat, upgrading, MGMP, higher learning and another activity. Its performing is done at school and outside school, even still effective reducing. Faced constraint are its reducing funds, equipment, its reducing is socialization sides on duty Education, teacher teaches knowledge area unsuitably with expertise it, partly teacher can't yet gain control technology, and its low willingness learns for amends. Key Words: Increasing Effectiveness, Professional and Teacher